“Of Slender Frame and Delicate Appearance”: the Placing of Laura Secord in the Narratives of Canadian Loyalist History - Morgan, Cecilia (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1994)
AbstractIn late nineteenth-century English Canada, particularly in Ontario, national identity and discourses of loyalty were frequently linked to Canadian history in general and. specifically, the legacy of the War of 1812. The commemoration of this war was especially important for those writers and historians who wished to maintain the country's link to Britain for, during this conflict, the colonial population had supposedly demonstrated their loyalty and devotion to Britain by helping to repulse American attacks. Both "national" historians and those who were members of the local historical societies that emerged in the 1880s wrote about the war and, in particular, male military heroes such as Major-General Isaac Brock. However, during this period a female symbol of national identity and loyalty to Britain also emerged, that of Laura Secord. While both male and female historians were interested in Secord, it was largely through the efforts of Anglo-Celtic, upper- and middle-class women that Secord became a heroine of the War of 1812. Many of these women were firm supporters of imperialism and the maintenance of British traditions in Canada, as well as being active in women's suffrage groups and other, related causes such as temperance. Their celebrations of Secord's walk and the narratives which they constructed about her contribution to Upper Canadian loyalty are significant not only for their recognition of women s contribution to Canadian history; they also help illustrate the relationships of gender, race, and imperialism in Canadian feminist and nationalist discourses.